2010
DOI: 10.5713/ajas.2010.10076
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Fe-soy Proteinate and MgO on Egg Production and Quality of Eggshell in Laying Hens

Abstract: This study investigated the effects of Fe-soy proteinate (Fe-SP) and magnesium oxide (MgO) dietary supplements on eggshell quality in laying hens. A total of 800 26-wk-old Hy-Line Brown hens were assigned to four dietary treatments: control (C), Fe-SP 100 (100 ppm Fe-soy proteinate), MgO (3 g MgO/kg diet), and Fe-SP 100+MgO. Each treatment had five replicates of 40 hens. The FT-IR (Fourier transform infrared) and XRD (X-ray diffraction) spectra of Fe-soy proteinate were different from those of FeSO 4 and soy d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 16 publications
4
24
0
Order By: Relevance
“…This result is in good agreement with the results of Park et al (2004) and Paik et al (2009). The production index was highest in the Cu-SP 100 group (Seo et al, 2010). Recent information suggests that chelated or complex trace elements may improve the bioavailability of minerals for pigs and poultry.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…This result is in good agreement with the results of Park et al (2004) and Paik et al (2009). The production index was highest in the Cu-SP 100 group (Seo et al, 2010). Recent information suggests that chelated or complex trace elements may improve the bioavailability of minerals for pigs and poultry.…”
Section: Resultssupporting
confidence: 89%
“…Fe content of egg-yolk was effectively increased by supplementing 100 ppm iron as Fe-SP for 5 wk (Seo et al, 2008). Eggshell color significantly improved due to supplementation of Fe-SP 100 (Seo et al, 2010). This result is in good agreement with the results of Park et al (2004) and Paik et al (2009).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…They concluded that eggshell colour generally gets lighter as the hen ages. Seo et al (2010) warned that feed supplemented with Fe soy proteinate significantly improved eggshell colour in brown-egg-laying hens. Further research by Dearborn et al (2012), explained that diet had a very limited effect on eggshell spectral reflectance, but individual females differed strongly and consistently from one another in eggshell colour.…”
Section: Discussionmentioning
confidence: 99%